SHORT INTEREST AND CORPORATE INVESTMENT: EXPLORING THE ROLE OF MARKET SENTIMENT AND FINANCIAL CONSTRAINTS - Khan , Sara; Brown, Liam (Ayden International Journal of Applied Economics, Finance and Accounting, 2025)
The perpetual debate regarding the rationality of stock markets remains a captivating and ongoing topic of inquiry. Existing literature broadly approaches this issue through two distinct frameworks: the classical and the behavioral perspectives. In the classical view, market efficiency prevails, where stock prices faithfully reflect changes in anticipated future cash flows or discount rates. Consequently, there should be no discernible relationship between share prices and corporate investment, provided that firms' fundamentals are sound. In stark contrast, the behavioral viewpoint posits that managers strategically time their equity issuances to capitalize on moments when stock prices become disconnected from underlying fundamentals, as exemplified by studies like Loughran and Ritter (1995) and Baker and Wurgler (2000). This study builds upon the works of De Long, Shleifer, Summers, Waldmann (1990) and Stein (1996) and the subsequent challenges posed by Baker, Stein, and Wurgler (2003 to challenge the classical perspective. Their theoretical and empirical framework introduces two investor categories: sophisticated informed investors and uninformed noise traders. Noise traders, influenced by biased beliefs, because stock prices to diverge from their intrinsic values. Stein (1996) asserts that investment decisions become contingent on investor sentiment if the required return on a share is a result of investor overestimation of future payoffs rather than the share's inherent risk. For instance, an overly optimistic investor climate may lead a manager to adopt an aggressive investment strategy to maximize the current share price